Incident gabapentin prescribing associated with opioid and benzodiazepine/Z-drug prescribing – a population-based longitudinal study in primary care - Linnet, Kristjan; Runolfsson, Bjarni Pall Linnet; Sigurdsson, Johann Agust; Gudmundsson, Larus Steinthor (Frontiers in Pharmacology, 2025)
AimTo investigate the association between long-term prescribing of opioids, benzodiazepines and Z-drugs, and the incidence of gabapentin prescribing.MethodsFrom January 2009 to December 2012, 219,800 patients contacted primary healthcare centres in the Reykjavik metropolitan area. Of these, 94,840 patients aged 10–69 years, met the inclusion criteria. Data on relevant ICD-10 conditions related to multimorbidity were retrieved from a comprehensive medical records database for the primary healthcare centres in the area run by the Primary Healthcare of the Capital Area. Information on redeemed prescriptions for the relevant drugs was obtained from the Medicines Registry of the Directory of Health. The subjects were divided into four groups based on long-term use of opioids, benzodiazepines (BZDs) and Z-drugs (Defined Daily Doses, DDDs). The incidence rate ratio (IRR) of gabapentin was assessed using Cox regression. The effect of certain chronic conditions and long-term use of selective serotonin reuptake inhibitors (SSRIs) was also explored. Finally, the amount and duration of future gabapentin use were examined.ResultsLong-term use of opioids, BZDs or Z-drugs was associated with an increased risk of future gabapentin use. Individuals with the highest use of opioids and benzodiazepines or Z-drugs, i.e., ≥30 DDDs BZDs or Z-drugs were most likely to initiate gabapentin therapy (IRR 7.18: 95% CI 6.50–7.93). These individuals also had the longest average duration of future gabapentin use.ConclusionThe rise in gabapentin prescriptions must be carefully monitored as prior history of opioids, benzodiazepines and Z-drugs may pose a risk of problematic gabapentin use.